TINJAUAN BERBAGAI INDIKATOR SOSIAL* - Singarimbun Masri (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1992)
This article delineates various indices: (a)The Physical Quality of Life Index(PQli) and the Subjective Composite Index used by the Indonesian Central Bureau of Statistics for making comparisons with the 27 provinces of Indonesia; (b) a revised version of PQLI by adding fertility as a new component developed by Sajogyo and Abustam; (c) the Non-Physical Quality Index, used by the office of the Minister of Population and Environment, and (d) the Human Development Index (HDI), contained in the UNDP: Human Development Report, 1991 and 1992